2010
DOI: 10.1002/ijc.25211
|View full text |Cite
|
Sign up to set email alerts
|

The health and economic effects of HPV DNA screening in The Netherlands

Abstract: We studied the health and economic effects of human papillomavirus (HPV) DNA testing in cervical screening using a simulation model. The key data source was a Dutch longitudinal screening trial. We compared cytological testing with repeat cytology (for borderline/mildly abnormal smears) to HPV testing with cytology triage (for HPV-positive smears), combination testing (combined HPV and cytology) and cytological testing with HPV triage (for borderline/mildly abnormal smears). We varied the screening interval fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 86 publications
(179 reference statements)
1
56
0
1
Order By: Relevance
“…Methods for calculating the ICER in six articles were; cost/ QALY (Mandelblatt et al, 2002b, Berkhof et al, 2010Chuck, 2010;Chow et al, 2010;Vijayaraghavan et al, 2009;2010a), in 13 studies the ICER were estimated by cost/LYG (Brown and Garber, 1999;Maxwell et al, 2002;Mandelblatt et al, 2002a;Goldie et al, 2001;2004;Kim et al, 2005;Bidus et al, 2006;Andres-Gamboa et al, 2008;Kulasingam et al, 2009;Levin et al, 2010;Sroczynski et al, 2011;Burger et al, 2012). Two studies did not report their ICER (Bistoletti et al, 2008;de Kok et al, 2012).…”
Section: Results By Outcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…Methods for calculating the ICER in six articles were; cost/ QALY (Mandelblatt et al, 2002b, Berkhof et al, 2010Chuck, 2010;Chow et al, 2010;Vijayaraghavan et al, 2009;2010a), in 13 studies the ICER were estimated by cost/LYG (Brown and Garber, 1999;Maxwell et al, 2002;Mandelblatt et al, 2002a;Goldie et al, 2001;2004;Kim et al, 2005;Bidus et al, 2006;Andres-Gamboa et al, 2008;Kulasingam et al, 2009;Levin et al, 2010;Sroczynski et al, 2011;Burger et al, 2012). Two studies did not report their ICER (Bistoletti et al, 2008;de Kok et al, 2012).…”
Section: Results By Outcomesmentioning
confidence: 99%
“…Chuck et al remarked that Pap smear screening every three years for all Canadian women and HPV triage for women older than 30 years with ASCUS were the most cost-effective strategies (Chuck, 2010 (Maxwell et al, 2002;Bidus et al, 2006). Berkhof et al (2010) in the Netherlands, indicated that starting screening with HPV triage with 5 years interval was the most cost effective strategies (Berkhof et al, 2010).Vijayaraghavan in South Africa reported that coscreening with HPV testing was less costly and the most effective strategy (Vijayaraghavan et al, 2009). Based on income we just found 5 articles in high income countries suggested starting age of screening below age 30 (Mandelblatt et al, 2002b;Kulasingam et al, 2009;Chuck, 2010;Vijayaraghavan et al, 2010a;Sroczynski et al, 2011)(Table1).…”
Section: Comparison Of Starting Age Of Screeningmentioning
confidence: 99%
See 3 more Smart Citations